Simplification Of Electronic-Based Policies On The Quality Of Driving License Services - Abdul Wahab Podungge; Susi Yanti Halawa; Dwi Indah Yuliani Solihin (Department of State Administration - Musamus University, 2024)
The Republic of Indonesia Police through the Research and Development Center has actually introduced an Electronic Based Government System which is the administration of government by utilizing information and communication technology to provide services to the community. However, this public service approach is not yet fully distributed across all Regional Police levels. The purpose of this article is to analyze the Simplification of Electronic-Based Policies on the Quality of Driving License Services. The research method used is a qualitative method. The data analysis used is an interactive model analysis which consists of three analysis components, namely: 1) Data Reduction; 2) Data Presentation; 3) Verify Data and Draw Conclusions. The results of the article show that: 1) The formulation of the policy, which includes how long the policy took to be made and the existence of public testing as well as understanding of personnel's understanding of the policy formulation, shows that it has been quite effective, because the placement of personnel in the Traffic Directorate of the Gorntalo Regional Police has gone through a scanning mechanism selected through a series of training -training at both the National Police Traffic Police level and the Gorontalo Regional Police level; 2) Policy implementation, which includes policy implementing resources, qualifications and monitoring systems for implementing policies, shows that it is not effective enough, because the characteristics of the community based on the 2021 Kominfo digital literacy survey, Gorontalo Province is ranked 29th or 6th from the bottom for the category of literate community technology . Apart from that, only 3 types of services are available, namely the Gorontalo City Police Satpas, Mobile SIM, and the Sinar Presisi application so they are not yet effective in reaching people outside Gorontalo City; 3) The results of the policy, which include objectives, quality, value of benefits and effectiveness of the resources used, show that they are not efficient enough, because the driving license service facilities are not yet capable, namely they do not have a standardized field for use in driving license practice tests, and complete facilities and supporting infrastructure. other ; 4) Outcome policy, which consists of feedback from the community receiving services and the consequences of the policy show that it is quite effective, because the service mechanism already refers to National Police Chief Regulation Number 5 of 2021 concerning the Issuance and Marking of Driver's Licenses